Level Up Students’ Fiqh Knowledge: How Gamification is Revolutionizing Ramadan Learning in Madrasah Ibtidaiyah - Ismail, Ismail; Tini, Tini; Rahmat, Rahmat (Universitas Muhammadiyah Enrekang, 2026)
Gamification has surfaced as a novel methodology aimed at augmenting student involvement and understanding across a multitude of educational spheres, notably within Islamic studies. This investigation scrutinizes the efficacy of gamification in augmenting Fiqh comprehension among third-grade pupils at Madrasah Ibtidaiyah Negeri (MIN) 2 Enrekang, concentrating particularly on the practices of Ramadan fasting and worship. Employing a mixed-methods research design, the study incorporated Fiqh Quest, a gamified board game, into the educational framework. The quantitative evaluation, predicated on pre-test and post-test metrics of 30 students, indicated a noteworthy enhancement in the average score from 58.18 to 74.76, with 90% of participants evidencing quantifiable knowledge advancements. Qualitative observations suggested a rise in motivation, enhanced collaboration among peers, and improved retention of Fiqh concepts, facilitated by gamified components such as points, badges, and leaderboards. The role of teacher facilitation was pivotal in synchronizing gamified activities with educational objectives. While the results underscore gamification’s capacity to metamorphose passive learning into active engagement, constraints include a limited sample size and a brief intervention duration, which may influence the generalizability of the findings. Subsequent research should investigate the scalability of gamification across varied educational contexts and evaluate its enduring effects on religious education. This study furnishes empirical data endorsing gamification as an efficacious pedagogical instrument in Islamic education, providing valuable insights for curriculum developers and educators aiming to elevate student understanding and engagement through interactive learning methodologies.